PERLAKUAN BERBAGAI KONSENTRASI PEG-6000 MEMBERIKAN PENGARUH BERAGAM TERHADAP PERKECAMBAHAN, DAN VIABILITAS VIGOR BENIH KEDELAI - WIJAYANTO, TEGUH; AMALIA, NURUL; AFA, LA ODE; BOTEK, MUHAMMAD (Jurnal Agroteknos, 2024)
This research aimed to determine the effect of PolyEthylene Glycol (PEG)-6000 concentration on the viability/germination and vigor of soybean seeds. The research was carried out at the Agrotechnology Laboratory, Agronomy Unit, Faculty of Agriculture, Halu Oleo University, Kendari. This research was carried out using a completely randomized design consisting of 5 treatments of PEG-6000 solution concentration and each was repeated 3 times. Each replication consisted of 3 samples so there were 45 experimental units. The variables observed were germination capacity, vigor index, maximum growth potential, growth simultaneity, and normal dry weight of the sprouts. The results of variance analysis showed that the concentration of PEG-6000 had a very significant influence on the observed variables of germination (%), vigor index (%), maximum growth potential (%), growth simultaneity (%) and normal dry weight of sprouts (g). The highest average germination capacity and maximum growth potential were obtained when administering a 6% PEG-6000 concentration, which was significantly different from the other concentrations. Meanwhile, simultaneous growth and the highest dry weight of normal sprouts were obtained at a PEG-6000 concentration of 12%, which was significantly different from the other concentrations.